Feasibility and efficacy of outpatient therapy with intermediate dose cytarabine, fludarabine and idarubicin for patients with acute myeloid leukaemia aged 70 or older. (16th March 2015) - Vives, Susana; Oriol, Albert; Piernas, Sònia; Brunet, Salut; Clapés, Victòria; Guardia, Ramon; Subirà, Maricel; Sierra, Jordi; Ribera, Josep‐Maria; ,
Abstract: Objectives: A multicentre prospective non‐randomised study of de novo acute myeloid leukaemia (AML) in patients aged ≥70 yr was designed to reduce toxicity and achieve acceptable complete remission (CR) rates. Methods: The outpatient treatment included induction with oral fludarabine, subcutaneous cytarabine and subcutaneous filgrastim (FAG). The patients received more induction cycles according to the response achieved. If there was no response to induction with FAG, the following induction cycle included oral idarubicin, subcutaneous cytarabine and subcutaneous filgrastim (IAG). Patients achieving CR received one intensification (FAG on response to previous FAG or alternatively IAG) and one consolidation cycle (IAG). Results: Thirty patients were enrolled from April 2004 to June 2007. The median age was 73 yr (range 70–77). Fifteen patients (50%) achieved CR. The 2‐yr DFS was 29% (95% CI, 5–47%), and the 2‐yr OS was 23% (95% CI, 12–35%). Twenty‐five of 69 cycles (36%) were managed on a completely outpatient basis. The median hospital stay per cycle was 10 d (95% CI, 3–25). Conclusions: This study demonstrates the tolerability and efficacy of a semi‐intensive treatment in elderly de novo patients with AML managed on an outpatient basis, without substantial toxicity.